The B Method at Siemens - Dolle, Daniel (Formal Methods Applied to Complex Systems: Implementation of the B Method, 2014)
Siemens SAS Industry Mobility is an international center of excellence for the creation of fully automatic subway systems and is a world leader in automated urban transport systems. The classic software development cycle involves specification, design, coding, testing and maintenance phases. These documents are translated into a formal model using B [ABR 96], known as the abstract model. The purpose of reviews is to identify faults in B models and their documentation as early as possible. Monitoring and analysis activities are also carried out with each evolution of Atelier B and the relevant transcoding tools. The implementation of automatic refinement has allowed us to multiply the size and complexity of our applications by 4, while reducing the size of development teams and the time needed to create our systems.